2021
DOI: 10.1093/jamia/ocab005
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a machine learning model predicting illness trajectory and hospital utilization of COVID-19 patients: A nationwide study

Abstract: Objective The spread of COVID-19 has led to severe strain on hospital capacity in many countries. We aim to develop a model helping planners assess expected COVID-19 hospital resource utilization based on individual patient characteristics. Materials and Methods We develop a model of patient clinical course based on an advanced multistate survival model. The model predicts the patient's disease course in terms of clinical sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
0
27
1
1
Order By: Relevance
“…The next generation of bed capacity predictions tools should use patient bed pathways with local information on length of stay. To the best of our knowledge, there are only three other published models available which used patient bed pathways [33][34][35]. The first one used the pathways "Ward", "Ward, ICU (not ventilated)", "Ward, ICU (ventilated)", "Ward, ICU (not ventilated), Ward", "Ward, ICU (ventilated), Ward" [33].…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The next generation of bed capacity predictions tools should use patient bed pathways with local information on length of stay. To the best of our knowledge, there are only three other published models available which used patient bed pathways [33][34][35]. The first one used the pathways "Ward", "Ward, ICU (not ventilated)", "Ward, ICU (ventilated)", "Ward, ICU (not ventilated), Ward", "Ward, ICU (ventilated), Ward" [33].…”
Section: Results In Contextmentioning
confidence: 99%
“…On the other hand, the advantage of our analysis is that our code and length of stay data are both publicly available (https://github.com/ qleclerc/COVID_bed_occupancy). As for the second model, it focused on machine-learning methods to estimate transition probabilities between the clinical states moderate/severe and critical, and is hence not comparable [34]. The third model is closely aligned to our own work here, as it uses multi-state methods to estimate length of stay using a local hospital and a national dataset from the UK [35].…”
Section: Results In Contextmentioning
confidence: 99%
“…The best results were found using XGBoost and achieved an AUC of 0.953 for a small dataset ( 15 ). In addition, the illness trajectory (moderate, severe, critical – states as defined by Israeli Ministry of Health) of COVID-19 patients was predicted by Roimi et al with an AUC of 0.88 using only patients' age, sex and day-by-day clinical state using a multistate Cox regression-based model ( 16 ).…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that risk factors, such as obesity, sex, and age, are highly correlated with adverse outcomes in COVID-19 patients. 2–7 Furthermore, recent studies suggest such risk factors also may affect certain aspects of COVID-19 progression, specifically disease onset, 8 hospital utilization, 9 and time-to-death. 10 However, the effects of individual patient characteristics on the entire course of COVID-19 progression during a patient’s hospitalization is still not well characterized.…”
Section: Introductionmentioning
confidence: 99%